Designing Plush Toys with a Computer. - Igarashi, Yuki; Igarashi, Takeo (Communications of the ACM, 2009)
We introduce Plushie, an interactive system that allows nonprofessional users to design their own original plush toys. To design a plush toy, one needs to construct an appropriate two-dimensional (2D) pattern. However, it is difficult for nonprofessional users to appropriately design a 2D pattern. Some recent systems automatically generate a 2D pattern for a given three-dimensional (3D) model, but constructing a 3D model is itself a challenge. Furthermore, an arbitrary 3D model cannot necessarily be realized as a real plush toy, and the final sewn result can be very different from the original 3D model. We avoid this mismatch by constructing appropriate 2D patterns and applying simple physical simulation to it on the fly during 3D modeling. In this way, the model on the screen is always a good approximation of the final sewn result, which makes the design process much more efficient. We use a sketching interface for 3D modeling and also provide various editing operations tailored for plush-toy design. Internally, the system constructs a 2D cloth pattern in such a way that the simulation result matches the user's input stroke. We successfully demonstrated that nonprofessional users could design plush toys or balloon easily using Plushie.